Implications of the germline variants of DNA damage response genes detected by cancer precision medicine for radiological risk communication and cancer therapy decisions. (5th May 2021) - Hosoya, Noriko; Miyagawa, Kiyoshi
ABSTRACT: Large-scale cancer-associated gene testing is now being rapidly incorporated into clinical settings, and is leading to incidental identification of the germline variants present in cancer patients. Because many cancer susceptibility genes are related to DNA damage response and repair, the variants may reflect not only the susceptibility to cancer but also the genetically defined radiation sensitivity of the patients and their relatives. When the presence of a certain germline variant increases the risk for developing radiation toxicity or radiation-induced secondary cancers, it will greatly influence the clinical decision-making. In order to achieve optimal radiological risk communication and to select the best cancer management for a given patient based on information from gene testing, healthcare professionals including genetic counselors, risk communicators and clinicians need to increase their knowledge of the health effects of various genetic variants. While germline loss-of-function mutations in both of the alleles of the DNA damage response genes cause rare hereditary diseases characterized by extreme hypersensitivity to radiation, the health effects of the carriers who have germline variants in one allele of such genes would be a matter of debate, especially when the significance of the variants is currently unknown. In this review, we describe the clinical significance of the genetic variants of the important DNA damage response genes, including ATM and TP53, and discuss how we can apply current knowledge to the management of cancer patients and their relatives from a radiological point of view.